2012
DOI: 10.2478/s11686-012-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of ascarid nematode infection (Toxascaris leonina and Toxocara cati) in captive Asiatic lions (Panthera leo persica)

Abstract: The objective of this study was to investigate the ascarid infection in Asiatic lions using scat samples, based on microscopic analysis, PCR amplification of the ITS-2 region of ribosomal DNA and sequence analysis of the amplicons. Microscopic analysis indicated the presence of eggs of Toxascaris leonina in eleven of the sixteen scat samples analysed and in one of these eleven scats eggs of Toxocara cati were also detected. In five of the scats eggs were not detectable. The presence of T. leonina in all the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…in non-human primates were reported to be more prevalent [10] [15] [19] [36]. The incidence of Toxocara cati and Toxascaris leonine in Lions in the current study was supported by Okulewicz et al [37], Pawar et al [38], Mukarati et al, [39]. In line with the present study Engh et al [40] reported that Toxocara canis was infecting hyena in the Masai Mara national reserve of Kenya while Luty [41] recovered it in the feces of foxes in the University zoological garden of south western Nigeria.…”
Section: Identification Of Species Of Gastrointestinal Parasitessupporting
confidence: 70%
“…in non-human primates were reported to be more prevalent [10] [15] [19] [36]. The incidence of Toxocara cati and Toxascaris leonine in Lions in the current study was supported by Okulewicz et al [37], Pawar et al [38], Mukarati et al, [39]. In line with the present study Engh et al [40] reported that Toxocara canis was infecting hyena in the Masai Mara national reserve of Kenya while Luty [41] recovered it in the feces of foxes in the University zoological garden of south western Nigeria.…”
Section: Identification Of Species Of Gastrointestinal Parasitessupporting
confidence: 70%
“…Zoological Park, Coimbatore (Varadharajan & Kandasamy 2000), Thrissur Zoo (Varadharajan et al 2001), Rajkot Zoo (Parsani et al 2001), captive at Ramgiri Estate, Wayanad (Ravindran et al 2006), MC Zoological Park (Singh et al 2006), Nandankanan Zoo (Mahali et al 2010), Nandan Van Zoo, Chhatissgarh (Thawait et al 2014) Coprology/ Molecular identification Nehru Zoological Park, Hyderabad (Pawar et al 2012) Leopard Panthera pardus Coprology Rajkot Zoo (Parsani et al 2001), M.C. Zoological Park (Singh et al 2006), Nandankanan Zoo (Mahali et al 2010), Nandan Van Zoo (Thawait et al 2014 Table 2.…”
Section: Coprologymentioning
confidence: 99%
“…Earlier in 2008, the complete mt genome of Toxocara spp., including Toxocara canis were sequenced and analyzed based on their mt genetic composition, protein-coding genes, and the location of tRNA genes [ 6 ]. Partial mt gene sequence of T. leonina from Asian lions was isolated, amplified and compared with those of other ascaridoid nematodes [ 7 ]. In addition, the complete sequences of mtDNAs of 3 Baylisascaris species ( B. schroederi, B. ailuri and B. transfuga ) were sequenced, and phylogenetically analyzed by maximum likelihood (ML), maximum parsimony (MP), and neighbor-joining (NJ) methods [ 8 ].…”
mentioning
confidence: 99%